Endemic angiosperm lineages in Mexico: hotspots for conservation - Sosa, Victoria; De-Nova, J. Arturo (Instituto de Ecología, A.C., 2012)
As a megadiverse country, Mexico harbors 4 to 8% of the flora of the world and of this, 51% is endemic. There is concern because several factors are impeding its conservation. In this paper, areas of endemism for the flowering plants of Mexico are identified to prioritize regions for conservation. To categorize zones for preservation, the approach followed takes biodiversity, weighted endemism and evolutionary history into account. Lineages of angiosperms, families, genera, and formal or informal groups within genera previously retrieved as monophyletic are selected to represent evolutionary history in equivalent spatial units. A database with 9416 entries based on specimens of species belonging to 259 monophyletic groups of angiosperms from Mexico was compiled, and their presence-absence recorded for every unit area. Species richness and weighted endemism index was calculated for each of these units. The results indicate that the majority of the regions with the highest indices of endemism have a dry climate with xeric vegetation, with the exception of two areas of tropical and temperate forests. They are: the northeastern rosette scrub in Nuevo León and Coahuila, gypsum grasslands in San Luis Potosí, the Sierra Gorda in Queréraro, Tolantongo in Hidalgo, the Tehuacán-Cuicatlán Valley in Puebla and Oaxaca, El Salto in Durango, Sierra de Quila in Jalisco, a western portion of the Balsas River Basin in Michoacán, Guerrero, Morelos and State of Mexico, the Tehuantepec area in Oaxaca, the Central Depression of Chiapas and El Triunfo in Chiapas. Some of the areas of endemism in the Chihuahuan Desert, Balsas River Basin, the Central Depression of Chiapas and the southern area of Oaxaca are not sufficiently protected. Approximately 340 species were microendemic, i.e. restricted to a single quadrat, and the Cactaceae account for the majority of the species on the Mexican Red List.